An Urban Partnership: Embracing Collaboration and Feedback - Kasey Dye; Margaret Wallace; Krystal Thompkins; Sande Dawes (The University of Alabama, 2022)
Our research-practice partnership is between an urban, high-poverty high school and a neighboring university. Our collaboration focused on establishing trusting relationships, cultivating a shared language between partners, and learning from and with each other throughout the partnership. When COVID-19 began and impacted schools around the world, our community partnership pivoted to address new issues faced by the high school. We evaluated our partnership through a retrospective pretest-posttest, mixed-methods research design. Teachers, instructional coaches, and school leadership were asked to reflect at the end of the program on the growth of the teachers with whom they worked, as well as their own growth. The evaluation evidence revealed that the partnership was beneficial for both teachers and instructional coaches. Teachers demonstrated growth in pedagogical and content knowledge, integration of technology and virtual tools, student engagement, and sense of professionalism. In this article, we will provide readers with ideas and resources for initiating their own partnership.